STRENGTHENING RELIGIOUS CHARACTER EDUCATION THROUGH THE IMPLEMENTATION OF TAHFIDZ AL-QURAN PROGRAMME - Riki, Riki; Permadi, Andi Taufik; Kusman, E; Sopandi, Sopandi; Veisyal, Andrian; Fauziyah, Fahrurozi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research is based on adolescent behaviour that does not reflect religious character. The purpose of this study is to describe and analyse the planning, implementation, evaluation and impact of the implementation of the Tahfidz Al-Quran programme to improve the religious character of students at SMPIT Ibrahim Ulul Azmi Bandung. The approach used in this research is a qualitative approach descriptive method, data collection techniques are carried out by interview, observation and documentation study. The results of this study indicate that 1) Programme planning is carried out by determining the form of the programme, programme objectives, determining the person in charge, time allocation, and material in the Koran tahfidz programme. 2) The implementation of the tahfidz programme is carried out using the Bi al-Nazhar method Kitabah method Sima'I method Takrir method Talaqi method (memorising). 3) The impact of the Quran Tahfidzul programme is very diverse. One of them is that students become more obedient to teachers. In addition, students also tend to be more disciplined in carrying out their daily activities